Pengaruh Waktu Pengadukan Terhadap Nilai Slump Dan Kandungan Udara Serta Kuat Tekan Beton - Khaidir, Trifad Mochd; Kurniawandy, Alex; Ermiyati, Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The compression strength of concrete can be affected by many factors. One of them are water-cement ratio and duration of mixing. The duration of mixing is usually only being estimated by workers and supervisors. In this research, the duration of mixing used are 2, 3, 4, 5, and 6 minutes with water-cement ratio 0,4 and 0,5. The 2 minutes duration of mixing being used as reference. From the result of the research, it can be seen that the value of water-cement ratio can also affect the value of air content and slump. The more liquid water-cement ratio of 0,5 can be produce a higher slump value. The air content and the slump may decrease as the duration of mixing increase, thus the 6 minutes duration has the smallest value compared to other duration. The highest compression strength is 33,12 MPa at 6 minutes for water-cement ratio 0,4 and 35,12 MPa at 5 minutes for water-cement ratio 0,5Keywords: water-cement ratio, compression strength, duration of mixing, air content, fresh concrete